The relation of stress coping strategies and self-handicapping strategies to the process of opiate addicts behavior changes - Jovanovic, Mirjana Ratko; Dickov, Aleksandra; Kajtez, Marija; Dickov, Veselin; Dragišić, Tatjana (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. During a progress of addictive behavior treatment, the strategies of coping with stress are engaged, but addicts may continue with self-handicapping behavior which is opposite to changing a problematic behavior. The aim of this study was to examine the stress coping (CS) strategies and self-handicapping (SH) strategies in relation to the process of addictive behavior change. Methods. In the descriptive clinical study, the sample of 200 consecutively recruited inpatient opiate addicts were explored. They underwent methadone therapy. The general information questionnaire, the Indicator of coping strategies (CSI), SH-questionnaire for assessing self-handicapping behavior (SH) and the University Rhode Island Change Assessment (URICA) questionnaire for the assessment of process of change were completed. The Student t-test, Pearson’s correlation coefficient and multiple regression analysis were applied. The SPSS for Windows was used and the p ≤ 0.05 defined as statistically significant. Results. Among the CS, there were significant correlations between avoiding problems strategy and all SH strategies (p ≤ 0.02). The social support was directly proportionate to the process of change (p = 0.03, β = 0.35). However, the process of change inversely correlated to internal handicaps in interpersonal relationships strategy (IHI) (p = 0.02; β = -0.54) and strategy of focusing to the problem (p = 0.00, β = -0.44). Conclusion. The significant positive predictor for the process of addictive behavior change was a strategy of social support, but focusing on the problem and the strategy of internal handicaps in achievement situations were significant negative predictors. The evaluation of motivation process and stress coping strategies could be useful for creation of improved tailored treatment of opiate addiction.